Insert geometry effects on surface roughness in turning process of AISI D2 steel - Taha, Z.; Lelana, Hani-kurniati; Aoyama, H.; Ghazilla, R.A.R.; Gonzales, J.; Sakundarini, N.; Sutono, Su.B. (Springer Verlag (Germany), 2010)
Surface roughness is an important parameter for ensuring that the dimension of geometry is within the permitted tolerance. The ideal surface roughness is determined by the feed rate and the geometry of the tool. However, several uncontrollable factors including work material factors, tool angle, and machine tool vibration, may also influence surface roughness. The objective of this study was to compare the measured surface roughness (from experiment) to the theoretical surface roughness (from theoretical calculation) and to investigate the surface roughness resulting from two types of insert, `C' type and `T' type. The experiment was focused on the turning process, using a lathe machine Colchester 6000. The feed rate was varied within the recommended feed rate range. We found that there were large deviations between the measured and theoretical surface roughness at a low feed rate (0.05 mm/r) from the application of both inserts. A work material factor of AISI D2 steel that affects the chip character is presumably responsible for this phenomenon. Interestingly, at a high feed rate (0.4 mm/r), the `C' type insert resulted in 40% lower roughness compared to the `T' type due to the difference in insert geometry. This study shows that the geometry of an insert may result in a different surface quality at a particular level of feed rate.